Feminism And Politics: A Study on Women's Representation in The Simultaneous Regional Elections 2018 in Makassar City - Bogheiry, Ali; Thaha, M. Thaha; Rahmah, Laila (Riviera Publishing, 2022)
Introduction: This study discusses the role of feminism and women's representation in general elections in Indonesia, especially what happened in the Simultaneous Regional Election of Makassar City in 2018, where two women were asked to become candidates for Deputy Mayor. Method: The author uses descriptive qualitative research and has conducted observations, direct interviews, documentation, audio, and visual materials. Result: The result of this study, based on the Final Voter List, is that women (507,487 female voters) are more optimal in exercising their voting rights in the Regional Head Elections in Makassar compared to men (483,349 people). Conslusion: Interviews show that women are highly expected in elections where society wants leaders who can understand mothers' and women's issues. This phenomenon is expected to ignite the spirit of women's participation in elections. Representation of women gives a new color to political strategy, especially in socialization and political communication activities.